2007
DOI: 10.1111/j.1348-0421.2007.tb03893.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Flagellin from Burkholderia pseudomallei Effects on an Increase in the Intracellular Calcium Concentration and Up‐Regulation of TNF‐α by Mononuclear Cells

Abstract: Using flow cytometry analysis, the flagellin of Burkholderia pseudomallei acts as a signalling inducer, and evokes an increase in the intracellular calcium ion concentration ([Ca2+]i) in human peripheral blood mononuclear cells (PBMC). The cells with increased [Ca2+]i segregate into the live monocyte gate and not into the live lymphocyte gates. The stimulated [Ca2+]i increase can be neutralized with anti‐flagellin antibodies. In the absence of [Ca2+], [Ca2+]i was increased rapidly in flagellin‐treated cells co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The present study confirmed the previous studies that flagellin is a component of B . pseudomallei that activates human innate and adaptive immune responses [ 8 , 25 27 ]. Our observation that rFliC activated HEK-Blue TM -hTLR5 cells confirmed that B .…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed the previous studies that flagellin is a component of B . pseudomallei that activates human innate and adaptive immune responses [ 8 , 25 27 ]. Our observation that rFliC activated HEK-Blue TM -hTLR5 cells confirmed that B .…”
Section: Discussionmentioning
confidence: 99%
“…Other cardiovascular medications are also known to influence the (innate) immune response. For example, certain calcium channel blockers were observed to interfere with both flagellin and LPS signalling [ 26 , 27 ]. Statins and aspirin demonstrate similar anti-inflammatory properties [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that Ca2 + signalling has a positive effect not only on the maturation of DCs, but also on the functions of DCs such as IL-12 secretion. These reports also suggest that the L-type Ca2 + channel exists in immature monocyte-derived DCs (iMDDCs), supported by the report that the L-type Ca channel exists in human peripheral blood mononuclear cells [22]. However, Faries et al showed that calcium signalling antagonized IL-12 production selectively from immature DCs activated with interferon (IFN)-g, tumour necrosis factor (TNF)-a and soluble CD40 ligand [23].…”
Section: Introductionmentioning
confidence: 71%